2021
DOI: 10.1177/10775595211054751
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Routine Abdominopelvic Ultrasound in Suspected Child Abuse in Children Under 2 years of Age: Review of 15 years of Experience

Abstract: In France, the current recommendation is to perform a routine abdominopelvic ultrasound in any child under 2 years of age who is suspected to have been abused. We retrospectively studied the relevance of this practice in our center over the past fifteen years. This was a descriptive, retrospective study of all children under 2 years of age who had been subject to suspected abuse. Abdominal images and reports were reviewed and cross-referenced with possible clinical and biological signs. Four hundred and five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…While this was reassuring, they also found that the percentage of cases representing low likelihood differed based on practice location after controlling for patient age, sex, race/ethnicity, twin/triplet status, injury types, and injury severity. Martin-Champetier et al (2022) assessed the findings of abdominal imaging (mostly routine ultrasound) in 405 children under 2 years of age with suspected physical abuse. Only four of those children were found to have traumatic abdominal injuries related to abuse, and these children all had clinical or biological features suggesting injury.…”
Section: Medical Diagnosismentioning
confidence: 99%
“…While this was reassuring, they also found that the percentage of cases representing low likelihood differed based on practice location after controlling for patient age, sex, race/ethnicity, twin/triplet status, injury types, and injury severity. Martin-Champetier et al (2022) assessed the findings of abdominal imaging (mostly routine ultrasound) in 405 children under 2 years of age with suspected physical abuse. Only four of those children were found to have traumatic abdominal injuries related to abuse, and these children all had clinical or biological features suggesting injury.…”
Section: Medical Diagnosismentioning
confidence: 99%